Intervensi Ceramah Video dan Ceramah Diskusi terhadap Pengetahuan dan Sikap Remaja dalam Kesehatan Reproduksi - Panjaitan, Arip Ambulan; Widagdo, Laksmono; Prabamurti, Priyadi Nugraha (Jurnal Promosi Kesehatan Indonesia, 2019)
Background: Adolescents are one of the high risk groups to face the cases of Unwanted Pregnancies, abortion, Sexually Transmitted Infections (STIs) including HIV and AIDS. Reproductive health education as an effort to prevent risky sexual behavior that is important to be delivered to adolescents. This study aims to determine the effect of reproductive health education models through lectures followed by videos and lectures with case discussions and roleplaying on increasing adolescent knowledge and attitudes in preventing risky sexual behavior.Method: This study is a quasy experiment with a pretest-posttest design with a control group. Data obtained using a structured questionnaire that has been tested for validity and reliability. The research subjects were class X students (ten) of SMAN 2 Sintang and SMAN 4 Sintang who were selected purposively as many as 120 people. The selection of samples using purposive sampling which recruited 40 people for each group, there were two treatment groups and one group for the control. Data were analysed using paired sample t-test and independent t-test.Results: The results of the study showed that there were no differences in the characteristics of the respondents from the two treatment groups and the control group, so that it was beneficial for this study. Likewise the level of knowledge and attitudes of respondent before intervention had no differences / homogeneous condition. Statistical results of paired sample t-test revealed that there were differences in the average score of knowledge and attitudes after intervention with p value 0,001. Intervention with lectures and discussions including role playing has increased the knowledge and attitudes scores of respondents higher than the lecture and video methods. It was concluded that intervention using lectures with case discussions including roleplaying has improved understanding of adolescents about reproductive health and sexuality so that this method was suggested to be used as an alternative for better reproductive health education for adolescents.Â